Electrically driven self‐healing polymers based on reversible guest–host complexation of β‐cyclodextrin and ferrocene. Issue 16 (23rd May 2013) - Chuo, Tsai‐Wei; Wei, Ta‐Chin; Liu, Ying‐Ling
ABSTRACT: A multifunctional ferrocene‐modified poly(glycidyl methacrylate) (PGMA‐Fc) and a difunctional β‐cyclodextrin derivative (bis‐CD) has been prepared for the construction of an electrically driven removable and self‐healing polymeric materials based on the complexation reaction between ferrocene and β‐CD groups. The chemical structures of PGMA‐Fc and bis‐CD have been characterized with Fourier transform infrared, 1 H nuclear magnetic resonance, and X‐ray photoelectron spectroscopy. The effects of electrical voltages and medium conductivity on the decrosslinking efficiency of the crosslinked PGMA‐Fc/CD polymer have been examined. The PGMA‐Fc/CD network has shown removable feature and properties for application as a reworkable crosslinked material. Moreover, the crosslinked PGMA‐Fc/CD sample has shown electrically driven self‐healing behavior. The self‐healing performance could be enhanced with wetting the sample to increase the electrical conductivity. As a result, the material could serve as a self‐healing agent for commercial painting products. Preparation and application of a novel and efficient self‐healing polymer have been demonstrated. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3395–3403 Abstract : The reversible complexation reaction of ferrocene and β‐cyclodextrin has been applied for preparation of electrically driven self‐healing polymers. Addition of 20 wt % of this agent to a commercial car‐painting product successfully brings self‐healing properties to the coating product.